Effects of intensive upright mobilisation on outcomes of mechanically ventilated patients in the intensive care unit: a randomised controlled trial with 12-months follow-up. (4th March 2021) - Amundadottir, Olof R.; Jónasdóttir, Rannveig J.; Sigvaldason, Kristinn; Gunnsteinsdottir, Ester; Haraldsdottir, Brynja; Sveinsson, Thorarinn; Sigurdsson, Gisli H.; Dean, Elizabeth
Abstract: Objective: To examine effects of intensive upright mobilisation on short- and long-term outcomes in critically ill mechanically ventilated patients. Methods: A randomised controlled trial compared patient outcomes after intensive twice-daily ( n  = 29) or daily mobilisation ( n  = 21). Patients in the intensive care unit (ICU), mechanically ventilated for over 48 hours, were randomly assigned to one of the two groups. Outcomes were duration of mechanical ventilation, ICU and hospital lengths of stay; health-related quality of life and physical function. Results: The twice-daily mobilisation group began upright mobilisation on day seven of ICU stay, and were mobilised upright on 31% of ICU days compared with the daily mobilisation group, who began upright mobilisation on day eight ( p  ≥ .05), and mobilised upright on 22% of ICU days ( p  = .03). No difference between groups was observed for any variable of interest across time-points over one year. Conclusions: The intensive twice-daily mobilisation group neither started upright mobilisation early nor yielded superior short- or long-term outcomes compared to the daily mobilisation group. Both groups showed poor physical health-related quality of life and exercise capacity one year after ICU discharge. Our findings support the need for targeted and tailored upright mobilisation in the ICU and after discharge.